KEDUDUKAN KERATON SURAKARTA BERDASARKAN UNDANG-UNDANG NOMOR 10 TAHUN 1950 TENTANG PEMBENTUKAN PROVINSI JAWA TENGAH - Imdat mustagfirin; Emilda Firdaus; Abdul Ghafur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Discourse Surakarta as the Capital is not a new discourse, the discourse is not separated from the long history of the founding of the city of Surakarta trip. The country has recorded the Provincial Solo or Surakarta Special Region (DIS). Surakarta or the existence of the Province of Special Region which began in August 1945 until June 16, 1946 consisting of the Special Region and the Special Region Mangkunagaran Kasunanan and governed jointly by the Regional KNI Surakarta, Susuhunan and Mangkunagara. In Juridical, that privilege Surakarta has been recognized in the Constitution of the Republic of Indonesia in 1945 on pasal18 B paragraph (1) which stated that the State recognizes and respects administration units, local special or that are regulated by law OF.This study is a normative legal research, the research done by examining material library (library research) .sedangkan legal material analysis method used in this research is descriptive. Once the data is collected in full and thorough, then the data are regrouped and adjusted to the type of data obtained, will be discussed and analyzed. The data used are primary data that ingredients binding law, as well as secondary data derived from primary legal materials, secondary and tertiary. Data was collected by the method of literature reviewResults of this study was the Establishment of Central Java province that includes Surakarta and simultaneously remove Surakarta as Special Region is based on Law 10 of 1950, it is contrary to facts other law, notably Article 18 of the Constitution of 1945 (before the amendment) in conjunction with Article 18B paragraph (1) of the Act of 1945 (amendment). Surakarta supposed privilege position may or may not be recognized back that is very dependent on the political will, the central government, parliament, local governments and communities Surakarta. efforts should be made to re-Surakarta recognition as a Special District, namely through the regional division or through judicial review of Law No. 10 of 1950 to the Constitutional Court. In view of a problem given the demands of the region's status as a special region can not be if only seen from the juridical aspect alone, of course other aspects also need to be considered, such as the historical 'disappearance' privilege status Surakarta and political factors surrounding it. Keywords: Position - Keraton - Surakarta